2009
DOI: 10.1074/jbc.m109.052779
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach for Experimental Target Identification of Hypoxia-induced miR-210

Abstract: miR-210 is a key player of cell response to hypoxia, modulating cell survival, VEGF-driven endothelial cell migration, and the ability of endothelial cells to form capillary-like structures. A crucial step in understanding microRNA (miRNA) function is the identification of their targets. However, only few miR-210 targets have been identified to date. Here, we describe an integrated strategy for large-scale identification of new miR-210 targets by combining transcriptomics and proteomics with bioinformatic appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
254
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(265 citation statements)
references
References 62 publications
9
254
1
1
Order By: Relevance
“…We then explored ROD1, also known as PTBP3, as a potential target of miR-210 in GBM cells. ROD1 has been confirmed as a direct but seedless target of miR-210 in HEK293 cells [4]. Immuno-precipitation analysis performed by Fasanaro et al [5] identified ROD1 as a miR-210-seedless transcript enriched in miR-210-containing RNA-induced silencing complexes.…”
Section: Discussionmentioning
confidence: 99%
“…We then explored ROD1, also known as PTBP3, as a potential target of miR-210 in GBM cells. ROD1 has been confirmed as a direct but seedless target of miR-210 in HEK293 cells [4]. Immuno-precipitation analysis performed by Fasanaro et al [5] identified ROD1 as a miR-210-seedless transcript enriched in miR-210-containing RNA-induced silencing complexes.…”
Section: Discussionmentioning
confidence: 99%
“…The other upregulated miRNAs, miR-130a, enhanced angiogenesis by modulating GAX (growth arrest-specific homeobox) and HOXA5 (homeobox protein Hox-A5), which are anti-angiogenic homeobox transcription factors [56] . Additionally, miR-210 was shown to be required for angiogenesis by targeting EphinA3 [57] , and miR146b, miR-197, and miR-625 expression was enriched in CD31 + endothelial populations derived from mouse ESCs [52] . Although the function of these miRNAs has been studied in cancer cells [58][59][60] , their role in the differentiation and functionality of ECs remains unknown.…”
Section: Endothelial Cell Differentiationmentioning
confidence: 99%
“…Therefore, several therapeutic trials regulating endogenous miRNA in vivo have been conducted [14][15][16]. miRNA also plays a crucial role in the pathogenesis of disease or trauma in locomotor organs [17][18][19][20][21]. As we known, vascular supply in tendons is very limited and is significantly reduced after injury or rupture.…”
Section: Introductionmentioning
confidence: 99%